Physical activity modifies the association of the composite dietary antioxidant index with all-cause mortality in the US osteoarthritis population - Zhang, Yiwei; Duan, Zhengwei; Lu, Hengli; Lu, Guanghua; Fu, Yuesong; Li, Guodong; Wang, Sen (Frontiers in Public Health, 2023)
Background: It remains unclear how antioxidant intake affects all-cause mortality in osteoarthritis (OA) patients. In this prospective cohort study, we aim to explore the association of the Composite Dietary Antioxidant Index (CDAI) with all-cause mortality and investigate the interaction of physical activity (PA) and CDAI on allcause mortality in OA populations.Methods: A total of 3197 adults with OA in the National Health and Nutrition Examination Survey (NHANES) from 2001-2018 were included in this study. Death outcomes were obtained from National Death Index (NDI) records. Multivariable Cox regression analyses with cubic spines were applied to estimate the association of CDAI with all-cause mortality. The interaction between CDAI and PA on all-cause mortality was further assessed in stratified analysis and interaction tests.The hazard ratios for all-cause mortality were 0.95 (0.77-1.17) for Q2, 0.75 (0.59-0.97) for Q3, and 0.71 (0.55-0.92) for Q4 (P for trend <0.001), compared with the lowest quartile of CDAI. A negative linear association was found between CDAI and all-cause mortality. In the stratified analyses, CDAI was negatively associated with all-cause mortality in the insufficient PA group. While in the low and sufficient PA group, there were nonlinear relationships of CDAI with all-cause mortality.A negative linear relationship was observed between CDAI and all-cause mortality in OA patients, and this association was significantly modified by PA. Higher intake of dietary antioxidants might be the interventional objective to reduce the risk of 3 all-cause mortality in the US OA population.